SERVICE QUALITY IN INSURANCE COMPANIES - Corneliu Bențe (University of Oradea, 2021)
Insurance services are a special category of services, characterized by a high standardization and at the request of customers to protect themselves from a number of financial losses that they may suffer as a result of risks. For this reason, it is very important that insurers provide quality services to customers. Customer satisfaction is paramount for attracting new customers and retaining existing ones, thus achieving a loyal customer base. They will recommend the insurance company and other potential customers if they are satisfied, thus increasing the market share of the insurance company. The quality of insurance services and the relationship between the insurance company and the client have been the subject of many studies over time, most often being followed by the impact that the quality of services has on their behavior. Starting from the identified problem, I set out in this paper to look at how consumers' perceptions of the quality of insurance services influence their perceptions of their relationship with the insurance company and implicitly their behaviour towards it. Starting from these approaches, we aimed in this paper to see what is the meaning given by the consumers of the insurance services of the company Allianz Țiriac to the concept of quality of insurance services. Our study consisted of an extensive process, carried out in several stages of work, namely: elaboration of the questionnaire addressed to the insurance company's clients, establishing the sample, collecting data based on questionnaires, centralizing and processing the data and interpreting the results. The case study took place over a month, on a sample of 300 people, most of the respondents are between 26 and 45 years old, who work in the private sector and came monthly between 1800-290 lei. The GAP analysis highlights some aspects of the services offered by Allianz Țiriac. A negative GAP highlights the unfavorable aspects of the services provided by the insurance company and raises an alarm about the situation of the company.